Закономірності фракціювання соняшникової олії пальмітинового типу при використанні допоміжних речовин - Куниця, Катерина Вікторівна; Литвиненко, Олена Анатоліївна; Гладкий, Федір Федорович (Технологический центр, 2013)
Стаття присвячена дослідженню закономірностей фракціювання соняшникової олії пальмітинового типу при використанні допоміжних речовин. Отримано дані щодо умов проведення фракційної кристалізації олії насиченого типу з допоміжними речовинами, а саме: етиловими ефірами насичених жирних кислот, монопальмітатом цукрози та дистильованими моноацилгліцеринами. Кінетику процесу фракціювання соняшникової олії пальмітинового типу оцінено за зміною фізичних показників фракцій.

The paper deals with studying the regularities of fractionation of sunflower oil of palmitic type using auxiliary substances. The data on the terms of fractional crystallization of saturated oil with auxiliary substances (crystallization initiators) was obtained and method of palmitic sunflower oil fractionation control is given. The obtained results can be used in solving the problems of control and management of crystallization in processing of fat stock and optimization of heat transfer processes which provide the required quality. It was determined that the proposed initiator leads to faster crystallization process. Rational quantity of the initiator for the process of fractional crystallization is 0.5 % to the weight of oil. Due to applying the specified amount of initiator, the crystallization duration is reduced by 3.4 times and constitutes 20 hours versus 68 hours without the initiator. The increase of oil crystallization rate in the presence of initiator leads to less coverage of the liquid fraction and allows achieving higher melting temperature of high-melting fraction. It was found that the value of optical density of the liquid fraction during crystallization varies to a greater extent and optical density is more sensitive to the changes in feedstock composition and crystallization conditions, while monitoring of the change in the value of refractive index during fractional crystallization is insufficient.
The regularities of fractionation of sunflower oil palmitic type the use of auxiliary substances
Keywords: фракційна кристалізація; показник заломлення; оптична густина; етилові ефіри; sunflower oil of palmitic type; fractional crystallization; refractive index; optical density